2014
DOI: 10.1111/hdi.12193
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury inChina

Abstract: China has a large population and bears a heavy burden of kidney diseases. Acute kidney injury (AKI) is increasingly prevalent in China and is associated with severe morbidity and mortality. The inadequacies of early diagnosis and management remain the major challenges to Chinese nephrologists. There is an urgent need for a nationwide, or even a global effort to increase an awareness of the devastating effects of AKI, to develop professional preventive strategies, as well as to achieve early diagnosis and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
(116 reference statements)
4
15
0
Order By: Relevance
“…AKI is one of the most serious complications with a reported mortality rate of 15% in hospitalized patients [15]. Our meta-analysis showed that HUA is a critical and potential risk factor for the incidence of AKI, not only in preoperative patients as reported previously but also in all hospitalized patients.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…AKI is one of the most serious complications with a reported mortality rate of 15% in hospitalized patients [15]. Our meta-analysis showed that HUA is a critical and potential risk factor for the incidence of AKI, not only in preoperative patients as reported previously but also in all hospitalized patients.…”
Section: Discussionsupporting
confidence: 64%
“…A current meta analysis found that the incidence of AKI after cardiac surgery was 22.3% around the world (95% CI 19.8-25.1) [2]. The incidence of PCI-induced AKI has been estimated between 2% and 30% depending mainly on baseline renal function, which is increasing along with the higher prevalence of CHD year by year [15, 29]. Our results suggest that higher pre-PCI SUA increased risk of AKI.…”
Section: Discussionmentioning
confidence: 68%
“…The mortality rate of the AKI patients in our study was 16.5%, consistent with other studies in China [20]. Most studies have consistently reported that the risk factors associated with a poor AKI prognosis include advancing age, cardiovascular disease, AKI stage, and so on [21].…”
Section: Discussionsupporting
confidence: 90%
“…Acute kidney injury (AKI) is a deterioration of renal function over a period of hours to days [1, 2]. It will cause severe morbidity if not handled properly [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…It will cause severe morbidity if not handled properly [1, 2]. Ischemic-hypoxia injury is the major pathological mechanism of AKI [14].…”
Section: Introductionmentioning
confidence: 99%